State-of-the-art green roofs: Technical performance and certifications for sustainable construction (2020)
Green roof systems, a technology which was used in major ancient buildings, are currently becoming an interesting strategy to reduce the negative impact of traditional urban development caused by ground impermeabilization. Only regarding the environmental impact, the application of these biological coatings on buildings has the potential of acting as a thermal, moisture, noise, and electromagnetic barrier. At the urban scale, they might reduce the heat island effect and sewage system load, improve runoff water and air quality, and reconstruct natural landscapes including wildlife. In spite of these significant benefits, the current design and construction methods are not completely regulated by law because there is a lack of knowledge of their technical performance. Hence, this review of the current state of the art presents a proper green roof classification based on their components and vegetation layer. Similarly, a detailed description from the key factors that control the hydraulic and thermal performance of green roofs is given. Based on these factors, an estimation of the impact of green roof systems on sustainable construction certifications is included (i.e., LEED—Leadership in Energy and Environment Design, BREEAM—Building Research Establishment Environmental Assessment Method, CASBEE—Comprehensive Assessment System for Built Environment Efficiency, BEAM—Building Environmental Assessment Method, ESGB—Evaluation Standard for Green Building). Finally, conclusions and future research challenges for the correct implementation of green roofs are addressed.